Comparative and phylogenetic analysis of complete chloroplast genomes of Phrynium s. s. and Stachyphrynium (Marantaceae) in China, including a new species - Lin, Zhiyi; Fan, Zhichao; Lan, Yaoqing; Fu, Lin; Xu, Feilong; Tong, Yi (Frontiers in Plant Science, 2025)
Plants of the genera Phrynium and Stachyphrynium traditionally used as ethnomedicine or for wrapping sticky rice dumpling in the tropical and south subtropical Asia, have a long history of ethnobotanical use. China represents the northernmost distribution of Marantaceae in Asia. Due to the notably similar leaf morphology between these genera, herbarium specimens are frequently misidentified, especially during the vegetative stages. Their morphological uniformity and unclear interspecific genetic relationships pose significant challenges to taxonomic classification and species identification. To date, systematic taxonomic revisions and phylogeny of their indigenous species remain lacking. In this study, we conducted comparative chloroplast genomes analyses of seven Phrynium and two Stachyphrynium species in China. The chloroplast genomes exhibited conserved structure, gene content, gene order and codon usage bias, but diverged in genomes size and the SC/IR boundaries. Four variable regions were identified as potential molecular markers for species identification. Phylogenetic analyses using CDS and nrDNA strongly support Phrynium and Stachyphrynium in China as two distinct monophyletic groups, with Phrynium subdivided into two clades. These findings advance our understanding of their molecular relationships and provide critical insights for identification, utilization, and conservation as medicinal plants. Finally, we describe and illustrate the new species Phrynium pyramidale Y. Tong & Z. Y. Lin.